Reciprocating compressors operation & maintenance - Bloch, Heinz P., 1933-; Hoefner, John J. (Houston, Tex. : Gulf Pub. Co., 1996)
For anyone responsible for purchasing, servicing, or operating reciprocating compressors, this book discusses the theory of operation and explains how to install, troubleshoot, overhaul, and repair all types of compressors. This broad comprehensive text offers practical details on how to purchase, service, operate, and maintain compressors used in any of the process industries such as pulp and paper, mining, food processing, pharmaceuticals.
Reciprocating compressors and their applications. Design and materials of reciprocating compressor components. Operation and maintenance of reciprocating compressors. Overhaul and repair of reciprocating compressors. Troubleshooting compressor problems. Preventive maintenance of reciprocating compressors. Safety in operation and maintenance. Appendix: Reciprocating compressor calculations. Index.
Includes bibliographical references (page 388) and index.
Keywords: Compressors; Compressors -- Maintenance and repair; Electronic books